1H‐NMR screening for the high‐throughput determination of genotype and environmental effects on the content of asparagine in wheat grain. Issue 1 (27th March 2015) - Corol, Delia I.; Ravel, Catherine; Rakszegi, Marianna; Charmet, Gilles; Bedo, Zoltan; Beale, Michael H.; Shewry, Peter R.; Ward, Jane L.
Summary: Free asparagine in cereals is known to be the precursor of acrylamide, a neurotoxic and carcinogenic product formed during cooking processes. Thus, the development of crops with lower asparagine is of considerable interest to growers and the food industry. In this study, we describe the development and application of a rapid 1 H‐NMR‐based analysis of cereal flour, that is, suitable for quantifying asparagine levels, and hence acrylamide‐forming potential, across large numbers of samples. The screen was applied to flour samples from 150 bread wheats grown at a single site in 2005, providing the largest sample set to date. Additionally, screening of 26 selected cultivars grown for two further years in the same location and in three additional European locations in the third year (2007) provided six widely different environments to allow estimation of the environmental (E) and G x E effects on asparagine levels. Asparagine concentrations in the 150 genotypes ranged from 0.32 to 1.56 mg/g dry matter in wholemeal wheat flours. Asparagine levels were correlated with plant height and therefore, due to recent breeding activities to produce semi‐dwarf varieties, a negative relationship with the year of registration of the cultivar was also observed. The multisite study indicated that only 13% of the observed variation in asparagine levels was heritable, whilst the environmental contribution was 36% and the GxE component was 43%. Thus, compared to some other phenotypic traits, breeding for low asparagine wheats presents a difficult challenge.